Modern Treatment Options for Epidermal Dysfunction at Atopic Dermatitis - Eduard T. Ambarchyan; Anastasiya D. Kuzminova; Vladislav V. Ivanchikov (Вопросы современной педиатрии, 2023)
Atopic dermatitis (AD) is a chronic inflammatory skin disease. Its crucial component of pathogenesis is malfunction of the epidermal barrier. Filaggrin protein and associated mutations in the filaggrin gene play one of the key roles in this problem. Nowadays new topical products (emollients) has been created and implemented into practice with the aim of more personalized approach and increased therapy efficacy in patients with AD. Such drugs would allow us to restore epidermal barrier function and to achieve elimination of disease symptoms.